Implementation of Linguistic politeness throughout Online Lectures via WhatsApp during the Covid-19 Pandemic - Halil, Nur Ihsan; Takwa; Musliha (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This research aims to investigate the implementation of politeness in the language of lecturers and students as well as students and students through online lectures at the Faculty of Teacher Training and Education, Universitas Sembilanbelas November Kolaka on the WhatsApp application. The research methodology used is descriptive qualitative with a focus on research, namely the fulfillment and violations of the principles of politeness in the language contained in online lecture conversations on WhatsApp. The data collection technique uses documentation or screenshots, and the data analysis technique uses content analysis methods with inductive procedures. The results indicate that the communication of lecturers to students and students to students based on the WhatsApp social network still pays attention to the principles of linguistic politeness in communication discourse. Based on the WhatsApp social network, students and lecturers can meet the principles of linguistic politeness, including maxim of wisdom, generosity, appreciation, simplicity, compatibility, and sympathy. However, there were also still some violations of the principle of politeness.